Synthesis of zeolite-carbon nanotube composite membranes - Lai, Zhiping (2010)
The objective of this project is to grow aligned carbon nanotubes (CNT) within the channels of an oriented zeolite layer to form a composite membrane for the purpose of gas separations. The project involves two phases. The first phase is to synthesize oriented AFI type of zeolite membranes with the straight channels aligned vertically to the membrane surface. Then in the second phase, carbon nanotubes are synthesized within the channels of the AFI membrane to form composite membranes. The task of the first phase was successfully achieved. Dense and highly c-oriented AFI membranes were successfully synthesized by a modified seeded growth technique. The synthesis procedure was systematically studied and optimum conditions for each step have been identified to improve the membrane quality. The dense and high c-oriented AFI membranes themselves will have potential applications in separations, membrane reactors, chemical sensors, and novel optical and electronic devices. Explorations of some of these potential applications are current on the way. Due to the challenges faced in both phases, only limited results for the second phase have been achieved so far. These include construction of a pyrolysis setup for synthesis of carbon nanotubes in a oriented AFI membrane and attempts to tailor the property of the AFI membranes to better assist the formation of carbon nanotube in the zeolite channels. Potential challenges for the second step have been identified. All of these efforts will provide a solid foundation to accomplish the task of the second phase in the near future.